Optimisation of the Application of Legal Aid for the Poor People in Sukabumi City - Haidan Angga Kusumah; Agus Rasyid ChandraWijaya (Universitas Lampung, 2019)
The background of this research is that access to the implementation of legal aid for the poor that is held by the state is still not effective, especially the poor in the area of Sukabumi City in terms of legal assistance by Legal Aid Providers is still not well coordinated. So research was carried out to describe descriptively about the optimisation of the application of legal aid for poor people in the area of Sukabumi City. The research method used is analytical descriptive, which describes the data from the relevant material existing and analyses it by referring to the Juridical basics. The results Showed that the optimisation of the application of legal aid for the poor people in the Sukabumi City area could be Tirrenus by government awareness in evaluating the condition of LBH in the region